Nueva variante de Bacillus toyonensis con cristales parasporales sin actividad pesticida - Sauka, Diego Hernan; Perez, Melisa Paula; Berretta, Marcelo Facundo; Palma, Leopoldo; Pinto, Matheus Moreira Dantas; Abdelgaffar, Heba; Jurat-Fuentes, Juan Luis (Asociación Argentina de Microbiología, 2024)
Poster y resumen